Varus Producing Distal Femur Osteotomy Alters Radiographic Measurements Related to Patellofemoral Instability: A Cadaver Study - Bond, Elizabeth C.; Cochran, Grant; Bulleit, Clark H.; Poehlein, Emily; Green, Cynthia L.; Wittstein, Jocelyn R. (The Journal of Knee Surgery, 2025)
Varus-producing distal femoral osteotomy (DFO) is an established procedure to correct genu valgum in patients with osteoarthritis and gait abnormalities. DFO has also been proposed for the treatment of patellar instability in patients with valgus alignment. However, it is not known how DFO affects parameters associated with patellar instability. This study evaluated radiographic changes after DFO with variable degrees of correction on six cadaveric knees, with the hypothesis that improving mechanical alignment would improve radiographic parameters related to patellar instability. Controlled laboratory is the study design. Six lower-limb cadaveric specimens were obtained after approval by the Institutional Review Board. A lateral opening wedge DFO was performed on each specimen with correction blocks of 6, 10, and 14 mm. The mechanical axis, tibiofemoral angle (mTFA), distal femoral angle (mDFA), Caton Deschamps index (CDI), insall salvati index (ISI), tibial tubercle to trochlear groove distance (TT-TG), and patellofemoral congruence angle (PFCA) were measured on computed tomography (CT) scans at baseline and after each correction block. At baseline, a mean varus alignment of the limbs was observed (mTFA: 2.7 ± 2.8 degrees, mDFA: 87.6 ± 1.0 degrees). The baseline patellar height was normal (CDI: 0.9 ± 0.2, ISI: 1.0 ± 0.1). Statistically significant decreases in mechanical axis and TT-TG distance and increases in mDFA and mFTA were found with increasing block size. The TT-TG distance was decreased by −1.6 mm (95% confidence interval [CI]: −2.27 to −0.86), −3.8 mm (95% CI: −4.8 to −2.8), and −4.0 mm (95% CI: −5.4 to −2.7) with a 6, 10, and 14 mm block, respectively. No differences were observed in patellar height when measured with CDI or ISI after any block size. In a cadaveric model, DFO significantly affects the mechanical axis and TT-TG distance. Specifically, this study found a mean decrease in TT-TG of −3.8 mm when performing a 10 mm opening wedge osteotomy. No changes in patellar height were observed.
Keywords: patellar instability; distal femoral osteotomy; genu valgum; radiologic measurements